2003
DOI: 10.1002/anie.200352630
|View full text |Cite
|
Sign up to set email alerts
|

Noble‐Metal Nanotubes (Pt, Pd, Ag) from Lyotropic Mixed‐Surfactant Liquid‐Crystal Templates

Abstract: A lot of attention is currently focused on nanosized tubular materials because of their unique physical properties and potential applications as gas and fluid paths or reservoirs in catalysis, fuel cells, sensors, and separation systems. [1] Since the discovery of carbon nanotubes, [2] there have been reports on a variety of inorganic nanotubes based on boron nitride, [3] metal sulfides, [4] metal borates [5] and metal oxides. [6] Besides high-temperature processes, [2][3][4][5] another approach that makes us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
132
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(135 citation statements)
references
References 32 publications
1
132
1
Order By: Relevance
“…Finally, the Pt species confining to the aqueous region of the molecular assemblies, are reduced to platinum atoms. The mixed surfactant LC template method can be extended to the synthesis of a wide range of 1-D inorganic or organic materials [100].…”
Section: -D Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the Pt species confining to the aqueous region of the molecular assemblies, are reduced to platinum atoms. The mixed surfactant LC template method can be extended to the synthesis of a wide range of 1-D inorganic or organic materials [100].…”
Section: -D Nanostructuresmentioning
confidence: 99%
“…Beside the successful synthesis of 1-D nanostructured materials [99,100], Kijima's group also prepared different Pt nanosheets in single or mixed surfactant LLC. In their report, growth of metal particles on the LLC, adsorbed at the solid/solution interface, would be greatly advantageous not only for elucidating the formation mechanism of metal nanotubes but also for producing unknown nanostructured metals.…”
Section: -D Nanostructuresmentioning
confidence: 99%
“…There are many investigations on carbon nanotubes, including synthesis, physical properties, application etc. 1 [10][11][12] nitrides (GaN, B 24 N 24 ), [13][14] Si, Te, noble-metal nanotubes (Ag, Au, Pt, Pd), [15][16][17] titanate nanotubes 18 and copolymer nanotubes, 19 but reports on the synthesis of ZnS nanotubes are scarce. 20,21 Most nanotubes that have been synthesized are open-ended linear tubes.…”
Section: Introductionmentioning
confidence: 99%
“…A series of further publications reported their advances in the electrochemical synthesis of various mesoporous metal films (Rh, Te, Sn, Se, etc.) in the presence of nonionic surfactant LLCs.[2]Recent work on preparing powders of mesoporous metals includes the work of Kijima et al, [3] who reported that noblemetal (Pt, Pd, Ag) nanotubes (i.e., a mesoporous metal powder) can be synthesized by using chemical reduction in mixedsurfactant LLCs, and that of Yamauchi et al [4] who successfully synthesized mesostructured nickel and nickel-cobalt alloys using electroless deposition in nonionic surfactant LLCs. In the literature many mesoporous metals, synthesized using both chemical and electrochemical templating methods in high-concentration surfactant LLCs, have been reported, however these are generally formed over small areas on microelectrodes or as powders in solution.…”
mentioning
confidence: 99%